Correlation between the effect of increasing body weight with plantar pressure and ankle-knee radiographic angle parameters changes - Dimas Triaryo; Luthfi Hidayat; Rahadyan Magetsari (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Understanding the biomechanical structure of the body is important to preventing and treating the musculoskeletal system problems. The increase in body mass index contributes to the elevated peak plantar pressure and decreased longitudinal arch of the foot. This condition, consequently, may cause mal-alignment of the lower extremity, leading to promote cartilage breakdown, osteophyte formation, subchondral bone hypertrophy, lead to progression of knee joint destruction and functional deficits. Objective: The aim of the study was to examine the correlation between body weight, plantar pressures, ankle and knee angle measurement parameters.Methods: The research study sample included 30 female who met inclusion and exclusion criteria. In order to evaluate the structural characteristic of plantar foot, we used the blueprint method on bare-foot and also when carrying 15 and 25 kilogram of load. Furthermore, to measure knee-angle parameters, we also performed a bilateral standing radiograph approach of lower extremity. Results: This study showed a significant correlation between BMI/Body mass index and HW/heel width (p = 0,00) with low positive correlation for both sides. Furthermore, BMI and PAW/plantar arch width (p = 0,00) showed a moderate positive correlation for both sides. In contrast to that, BMI and MFA/mid-foot area (p = 0,00) showed a moderate positive correlation for the right side but low positive correlation for the left side. Another measurement such as BMI and AI/arch index (p = 0,00) had a strong positive correlation on the right side and moderate positive correlation on the left side. Moreover, BMI and AAL/Ankle angle alignment (p = 0,00) revealed a strong positive correlation for both sides, BMI and XCTP/trans-condylar tibial plateau angle (p < 0,05) had a low positive correlation for both sides, meanwhile BMI and AA/ankle angle (p = 0,00) showed a low positive correlation for both sides. Conclusion: Increasing axial load was statistically significant correlated with increasing plantar pressure and ankle-knee radiographic angle parameter. The results also revealed that increasing axial load was found to have strong correlation to the arch index (AI) and ankle angle alignment (AAL). It was a compensatory phenomenon, which can cause structural disturbances and function of the lower limb.